Improved survival in metastatic germ-cell cancer. (17th November 2017) - Fankhauser, C D; Sander, S; Roth, L; Beyer, J; Hermanns, T
Abstract: Background: The prognostic score of the International Germ-Cell Cancer Collaborative Group (IGCCCG) in metastatic germ-cell cancers (mGCC) relies on treatments delivered before 1990. It is unclear, if this score is still relevant to contemporary cohorts of patients who receive modern-type chemotherapy and supportive care. Patients and methods: All patients who underwent cisplatin/etoposide-based first-line chemotherapy for mGCC at the University Hospital Zurich (USZ) between 1991 and 2016 were identified retrospectively. Clinical characteristics were extracted from medical charts and patients classified according to the IGCCCG score. International germ cell consensus classification: a prognostic factor-based staging system for metastatic germ cell cancers. J Clin Oncol 1997; 15: 594–603.). Progression-free survival (PFS) and overall survival (OS) probabilities at 5 years served as outcome parameters. Results: The study cohort consisted of 204 patients at a median age of 32 years and a median follow-up of 4.2 years. According to the IGCCCG score, PFS in the contemporary USZ cohort was 71% overall: 83% for good-risk, 69% for intermediate-risk and 30% for poor-risk patients, P < 0.001. OS for the entire cohort was 88%. In respect to OS, we observed no difference between good- and intermediate-risk patients (94% versus 91%, P = 0.62), but a statistically significant difference between those two risk groups and poor-risk patients, who had an OS of only 65%, P < 0.001. Conclusions: Within the contemporary USZ cohort of mGCC patients no improvements in PFS probabilities were observed compared with the ones predicted by the IGCCCG score for any prognostic category, but marked improvements in OS probabilities for intermediate- and poor-risk patients, possibly due to better salvage treatments.